2012
DOI: 10.1002/dc.22940
|View full text |Cite
|
Sign up to set email alerts
|

Immediate cytology improves accuracy and decreases complication rate in real‐time computed tomography‐guided needle lung biopsy

Abstract: Computed tomography-guided percutaneous transthoracic needle biopsy (CTNB) of the lung is a well-established diagnostic technique for the evaluation of thoracic lesions. At our institution, we have performed real-time CTNB using automated biopsy needles since 1998 and we introduced immediate cytology in 2004. We evaluate immediate cytology in CTNB to increase the diagnostic accuracy and to reduce the number of inadequate specimens. We retrospectively reviewed a consecutive series of 270 patients (group A: 98 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Liquid‐based smear samples should immediately be placed in digestive or preservative solutions and sent to the laboratory for further processing according to the operating procedures. Both rapid on‐site evaluation of cytology (ROSE) and on‐site imprint cytology involving cytopathologists can improve diagnostic accuracy . Specimens for histopathological examination should be fixed immediately after they are obtained by placing the samples in a 10% neutral buffered formalin fixative.…”
Section: Biopsy Proceduresmentioning
confidence: 99%
“…Liquid‐based smear samples should immediately be placed in digestive or preservative solutions and sent to the laboratory for further processing according to the operating procedures. Both rapid on‐site evaluation of cytology (ROSE) and on‐site imprint cytology involving cytopathologists can improve diagnostic accuracy . Specimens for histopathological examination should be fixed immediately after they are obtained by placing the samples in a 10% neutral buffered formalin fixative.…”
Section: Biopsy Proceduresmentioning
confidence: 99%
“…The pooled incidence of non-diagnostic results was 6.8% (95% CI, 6.0–7.6%; I 2 = 0.91; 24668 biopsies in 106 studies) 4,68,11,12,19,22–24,26–35,38,4042,44–49,52,54,55,5962,65–67,6986,89,91–97,99103,106113,115–118,120,122126,128133,135143,146,147 .…”
Section: Resultsmentioning
confidence: 99%
“…With regard to other pathology findings, the malignancy rate was the highest for specific malignancy (99.8%, 95% CI, 99.7–99.9%; I 2 = 0.00; 11,884 biopsies in 114 studies) 3,4,69,11–23,2568,70,72–76,78,79,8186,88,90–93,96,99101,103105,108,113–115,118–120,124,126130,132,134,138147 , followed by atypical cells (91.1%, 95% CI, 87.8–94.5%; I 2 = 0.23; 312 biopsies in 41 studies) 4,9,13,14,1720,26,27,29,30,34,37,41,42,46,47,53,64,66,70,74–76,79,85,86,8991,98,101,104,108,115,120,126,129,144,147 , AAH (88.9%, 95% CI, 76.7–100.0%; I 2 = 0.31; 18 biopsies in 6 studies) 8,76,84,126,128,138 , non-specific benign results (20.6%, 95% CI, 17.8–23.4%; I 2 = 0.96; 2574 biopsies in 64 studies) 4,6,8,11,12,19,22,23,26–28,…”
Section: Resultsmentioning
confidence: 99%
“…CNLB-related complications mainly focus on pneumothorax, bleeding and/or a combination of both (25)(26)(27)(28)(29). The results showed that the incidence of complications in the experimental group was apparently lower than in the control group, though the findings did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 95%